A haunted girl - Sacks, Ethan; Sacks, Naomi (Image Comics, 2024)
"Cleo, a 16-year-old adopted Japanese American whose anxiety and depression drive her to suicidal thoughts, is fresh out of the hospital and trying unsuccessfully to reintegrate back into her old life. What she doesn't know is that her real struggles are just beginning as she finds herself encountering an increasingly terrifying succession of ghosts. Is she losing her grip on reality... or is the explanation much, much worse?" --